The Figure of the ‘Mexican Impasse’ as Micro-representation - Levasseur , Hélène (E|C, 2024)
This paper discusses the utilisation of Mexican standoff in cinema to represent a battle at a reduced scale. We will use narrative semiotics to determine the importance of the Mexican standoff in the development of action in the narrative program. Studying the spatial dimension, we will try to understand how the battlefield within the Mexican standoff defines itself in opposition to the notion of territory. Furthermore, we will see the impact the change of scale has on the strategies and how the notions of interactions and strategies help us analyse the negotiation to resolve the problem of status quo. For this purpose, we will analyse the cinematographic representation of the sensorial dimension of the battle by the subject.